Description of the female of Catocala becheri (Lepidoptera: Erebidae) - Volynkin, Anton V.; Borth, Robert J.; Didenko, Sergei; Saldaitis, Aidas (Zootaxa, 2017)
Catocala becheri Borth, Kons & Saldaitis, 2017 was recently described from Central Vietnam. It is a member of a morphologically well-defined group including Catocala intacta Leech, 1889 and Catocala hoferi Ishizuka & Ohshima, 2003 which both differ from C. becheri in wing pattern and male genitalia. (Borth et al. 2017). Recent collecting has provided additional specimens, including the first female C. becheri, described below.